Peluang Pengembangan Ekonomi Berbasis Syariah Melalui Badan Usaha Milik Desa (BUMDes) : Studi Kasus BUDes Kel. Tanjug Ria Kec. Jayapura Utara Kab. Jayapura - Novie Citra Arta, Deddy (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2024)
In a sharia-based economy there is a profit and non-profit orientation. Sharia financial institutions, sharia business entities, pawnshops, insurance, and all forms of transactions based on sharia values ​​are a form of sharia-based economy with a profit orientation. Meanwhile, Islamic philanthropic institutions such as zakat institutions, waqf, and others are a form of Islamic economics with a non-profit orientation. The growth of these two segments has increased since the emphasis on regulations by the government and public awareness of the importance of Sharia economic practices themselves. However, the growth of one segment of the Islamic economy is less than balanced. The dominance of the growth of sharia financial institutions makes the growth of sharia business entities less visible. This research was conducted to examine opportunities for implementing Islamic economics in Village-Owned Enterprises (BUMDes). The research results show that the opportunity for implementing Islamic economics in BUMDes is very large. Apart from that, transaction contracts can be applied to BUMDes. Case Study in BUMDes in Kelurahan. Tanjung Ria , Kec. North Jayapura Kab. Jayapura